A single-cell Arabidopsis root atlas reveals developmental trajectories in wild-type and cell identity mutants - Shahan, Rachel; Hsu, Che-Wei; Nolan, Trevor M.; Cole, Benjamin J.; Taylor, Isaiah W.; Greenstreet, Laura; Zhang, Stephen; Afanassiev, Anton; Vlot, Anna Hendrika Cornelia; Schiebinger, Geoffrey; Benfey, Philip N.; Ohler, Uwe (Developmental cell, 2022)
In all multicellular organisms, transcriptional networks orchestrate organ development. The Arabidopsis root, with its simple structure and indeterminate growth, is an ideal model for investigating the spatiotemporal transcriptional signatures underlying developmental trajectories. To map gene expression dynamics across root cell types and developmental time, we built a comprehensive, organ-scale atlas at single-cell resolution. In addition to estimating developmental progressions in pseudotime, we employed the mathematical concept of optimal transport to infer developmental trajectories and identify their underlying regulators. To demonstrate the utility of the atlas to interpret new datasets, we profiled mutants for two key transcriptional regulators at single-cell resolution, shortroot and scarecrow. We report transcriptomic and in vivo evidence for tissue trans-differentiation underlying a mixed cell identity phenotype in scarecrow. Our results support the atlas as a rich community resource for unraveling the transcriptional programs that specify and maintain cell identity to regulate spatiotemporal organ development. [Display omitted] •scRNA-seq of >110,000 cells produced a comprehensive Arabidopsis root atlas•Gradual, overlapping waves of gene expression underlie development of all cell types•Developmental trajectories enable visualization of cell specification events•scRNA-seq of the scarecrow mutant reveals a cell identity change occurs over time How do transcriptional networks regulate organ development? Using scRNA-seq, Shahan and Hsu et al. produced an Arabidopsis root atlas, revealing gradual gene expression changes underlying differentiation of cell types and candidate regulators of cell fate. The atlas enabled interpretation of smaller scRNA-seq datasets and revealed new phenotypes in developmental mutants.